2009
DOI: 10.1007/s10059-009-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Backbone Resonance Assignment of a Proteolysis-Resistant Fragment in the Oxygen-Dependent Degradation Domain of the Hypoxia Inducible Factor 1α

Abstract: Hypoxia-inducible factor 1alpha (HIF1alpha) is a transcription factor that plays a key role in the adaptation of cells to low oxygen stress and oxygen homeostasis. The oxygen-dependent degradation (ODD) domain of HIF1alpha responsible for the negative regulation of HIF1alpha in normoxia is intrinsically unfolded. Here, we carried out the backbone (1)H, (15)N, and (13)C resonance assignment of a proteolysis-resistant fragment (residues 404-477) in the HIF1alpha ODD domain using NMR spectroscopy. About 98% (344/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, the physiologically expressed HIF-1α is degraded by the body within minutes under normoxic conditions. It was found that the mechanism by which HIF-1α is rapidly degraded by the organism under normoxic conditions is the HIF-1α subunit functional region (CDS region) encoding 826 amino acids, which has an oxygen-dependent degradation structural domain (ODD) consisting of more than 200 amino acids, Hydroxylation of the 402nd and 564th proline residues in the ODD of the HIF-1α molecule catalyzed by proline hydroxylase (oxygen is required for this hydroxylation process), and the hydroxylated HIF-1α is rapidly degraded by ubiquitin protease (Jin et al, 2009;Kim et al, 2009;Wei et al, 2010). In contrast, under hypoxic conditions, because proline 402, 564 cannot be hydroxylated, HIF-1α accumulates and is transferred to the nucleus, where it activates the hypoxia-responsive gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiologically expressed HIF-1α is degraded by the body within minutes under normoxic conditions. It was found that the mechanism by which HIF-1α is rapidly degraded by the organism under normoxic conditions is the HIF-1α subunit functional region (CDS region) encoding 826 amino acids, which has an oxygen-dependent degradation structural domain (ODD) consisting of more than 200 amino acids, Hydroxylation of the 402nd and 564th proline residues in the ODD of the HIF-1α molecule catalyzed by proline hydroxylase (oxygen is required for this hydroxylation process), and the hydroxylated HIF-1α is rapidly degraded by ubiquitin protease (Jin et al, 2009;Kim et al, 2009;Wei et al, 2010). In contrast, under hypoxic conditions, because proline 402, 564 cannot be hydroxylated, HIF-1α accumulates and is transferred to the nucleus, where it activates the hypoxia-responsive gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…NMR spectroscopy is a powerful tool that provides detailed structural characteristics of partially folded proteins or intrinsically unstructured/unfolded proteins (IUPs) at the amino acid residue level (Chi et al, 2005;Kim et al, 2009;Lee et al, 2000;2012). IUPs are peculiar proteins that are affiliated with a variety of biological functions including transcription, translation, and A B cell signaling as well as critical diseases such as prion diseases, amyloidgenesis, cancers, and viral infections but do not form unique three-dimensional structures under non-denaturing conditions (Chouard, 2011;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%